2023
DOI: 10.2340/17453674.2023.12358
|View full text |Cite
|
Sign up to set email alerts
|

In old men Scheuermann’s disease is not associated with neck or back pain: a Swedish cohort study

Anette Jönsson,
Henrik Damm,
Mehrsa Hofvander
et al.

Abstract: Background and purpose: Scheuermann’s disease is characterized by kyphosis and frequently mild back pain. As the level of kyphosis may progress over time, also the level of pain may increase. We evaluated the prevalence of Scheuermann’s disease, and their pain, in Swedish elderly men.Patients and methods: The Osteoporotic Fractures in Men (MrOS) Study Sweden (n = 3,014) is a population-based prospective observational study of community-living men aged 69–81 years. At baseline, participants answered a questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Jonsson et al 74 evaluated the prevalence of Scheuermann’s disease, and their pain, in Swedish elderly men. In his study, among men with SD and back pain, none reported severe pain, 57% moderate, and 43% mild, compared with 7%, 50%, and 44% in those without SD.…”
Section: Scheuermann’s Diseasementioning
confidence: 99%
“…Jonsson et al 74 evaluated the prevalence of Scheuermann’s disease, and their pain, in Swedish elderly men. In his study, among men with SD and back pain, none reported severe pain, 57% moderate, and 43% mild, compared with 7%, 50%, and 44% in those without SD.…”
Section: Scheuermann’s Diseasementioning
confidence: 99%